IMPLEMENTASI NAIVE BAYES UNTUK SISTEM PREDIKSI MAHASISWA BERPRESTASI - Desi Puspita; Siti Aminah (JITEK (Jurnal Ilmiah Teknosains), 2022)
An outstanding student is someone who is officially registered in taking lessons at a university who has succeeded in achieving a level of success about a goal because of a learning effort. The problem at the Pagar Alam Institute of Technology (ITPA) is that the current process of determining outstanding students is still manual. The purpose of this research is to apply the NaÃ¯ve Bayes method to predict student achievement. The attributes used in determining outstanding students are GPA, Organization, and Charter. The system development method used in this research is Waterfall which consists of Analysis, Design, Coding, Testing and the testing method carried out in this study is Blackbox Testing. The results of the research using the NaÃ¯ve Bayes algorithm with nave Bayes calculations, for example, x has GPA criteria> 3.65, there is an organization, there is a charter. System testing with blackbox testing is based on the results of questionnaires filled in by experts, who get a score of 4.5 with very valid information. Then the results of the calculation of achievement get a value of 0.015625, while the description of non-achievers gets a value of 0. Thus, the probability value of the class with achievement is greater than that of the class with no achievement. Then x goes to the high-achieving class.